Alien and cryptogenic Foraminifera in the Mediterranean Sea: A revision of taxa as part of the EU 2020 Marine Strategy Framework Directive - STULPINAITE, RUTA; HYAMS-KAPHZAN, ORIT; LANGER, MARTIN R. (Mediterranean Marine Science, 2020)
The human-mediated translocation of marine alien species beyond their natural ranges started as early as people began navigating the sea and is of growing concern to nature conservation. The Mediterranean Sea is among the most severely affected areas by biological invasions, a phenomenon that has been fostered by the opening and recent extension of the Suez Canal, the transport and release of ballast water, aquaculture and aquarium trade, ichthyochory and other active or passive dispersal mechanisms. The increase of marine invasions has stimulated considerable research, but for some important groups, in particular microorganisms, data are still limited. In this paper we have reviewed the current status of marine alien foraminifera in the Mediterranean Sea. Our survey includes a comrephensive taxonomic revision of previously recognized alien taxa, and new information obtained from the fossil record and from molecular studies. Our survey and reexamination of alien benthic foraminifera yielded a total of 44 validly recognized species and two species of cryptogenic taxa and reduces the number of previous recordings. The revised list includes both larger symbiont-bearing and smaller benthic foraminifera, including 16 hyaline-perforate, 3 agglutinated and 25 porcelaneoustaxa. The vast majority of alien foraminifera recorded so far have become established in the Eastern and Central Mediterranean Sea, indicative for translocation and introduction via the Suez Canal pathway. Only one species, Amphistegina lobifera, causes significant ecological impacts and fulfills the criteria to be considered as an invasive alien. This species is a prolific carbonate producer, and displays extreme forms of ecosystem invasibility with capabilities to reduce native diversity and species richness. The proliferation and rates of recently observed range extensions, track contemporary sea surface temperature increases, provide strong support for previous species distribution models, and corroborate findings that rising water temperatures, global climate change and the extension of climate belts are major drivers fueling the latitudinal range expansion of larger symbiont-bearing and smaller epiphytic foraminifera. Intensified efforts to study alien foraminifera on a molecular level, in dated cores and in ballast water are required to trace their source of origin, to identify vectors of introduction and to verify their status as true aliens.